"Pannonian" Benedictine Possessions in the 6th Century - Jarak, Mirja (Array, 1998)
In the article is examined very often cited statement about early Benedictine possessions in Pannonia. The "Pannonian" Benedictine possessions were, in reality, late Roman settlements in the 6th century.